An Analytical Study of NAFDAC’s Influence on the Safety and Market Dynamics of Aporo-Epa Ijebu in South-West Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2026)
The study examines National Agency for Food and Drug Administration Control (NAFDAC) with particular reference to the role of NAFDAC established by Decree 15 of 1993 (as amended) and charged with responsibility to control and regulate the manufacture, importation, advertisement, sales and use of food, drugs, chemicals, cosmetics, detergents, medical devices and all drinks with the view of protecting and safeguarding the citizens against consumption of hazardous and uncertified food, drugs and other related products. The study analyses primary data against the background of the objective. Evidence available indicates that consumer protection in Nigeria like most less developed countries remained at the lowest ebb. The study observed that although NAFDAC recognized the right of consumers but not specifically provide avenue on how these rights should be enforced as they are merely implied and subsumed with the function of the agency. Meanwhile, consumers’ awareness of their protection laws is low, even in case of obvious infringement. This implies that NAFDAC should be more proactive in safeguarding the welfare of Nigerians. The study employed Focus Group Discussion (FGDs) to elicit information from illiterates that more vulnerable while secondary data are sourced from textbooks, journals, publications and internet facilities.